A cause for concern: Forthcoming regulatory competition in the burgeoning NewSpace industry. (October 2021) - Simon, Steve
Abstract: Entrepreneurs and blue-chip corporations alike are seeking to capitalize on outer space's bountifulness, setting the NewSpace industry's growth ablaze and establishing an engine for an economic and technological revolution. However, meaningful impediments that could stifle the industry's growth are still present. The wide array of newly forming opportunities, pursued by a myriad of actors with various interests, encourages national legislatures to regulate where current international law leaves uncertainty. Such encouragement has created a landscape of conflicting national legislations, which thereby constructs an environment of regulatory competition as states vie for the attention of the NewSpace industry. This paper assesses some of the regulatory competitions already underway as well as provides insights into likely future competitions as technology improves and interest in NewSpace grows. Ultimately, this paper finds and warns of the effects of these competitions; specifically that, in many cases, the rise of regulatory competition threatens to lower the standards of governing policies. In such circumstances, this paper foresees the growing possibility of inhibiting the development of NewSpace, an unsettling outcome and a worthy cause for concern. Highlights: There is a lot of uncertainty when applying the current space law to private actors. Uncertainty slows growth & impacts flow of private capital creating legal vacuum. Governments writing national laws to fill vacuum creates regulatory competitions. Regulatory competitions has & will lower industry standards hurting NewSpace growth. Some international agreements, modernized for NewSpace, are needed.